Disain LieYo Hidro Generator Explorasi Energi Arus Lepas Pantai - Jasa, Lie; Ardana, I Putu (Majalah Ilmiah Teknologi Elektro; Vol 16 No 3 (2017): (September - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2017.v16i03p07, 2018)
Sea currents are one of these renewable energy sources that have not been developed, because they cost a lot and the capacity of energy produced is small. The presence of corrosion factors of sea air to the material containing the iron element of the material used must be of stainless steel. The existence of coral reefs that grow on objects submerged in the sea in a long time. Based on the above problems, the researcher wanted to develop an idea to make LieYo hydro generator. The idea of generating this generator is based on a magnetic ball placed on a vertically mounted pipe and each pipe is paired with a coil, a magnet ball that moves freely up and down in the pipe due to the wobble of the sea surface. Movement of magnetic spheres up and down causing the coils to receive magnetic field lines, the movement of the magnetic sphere will form an electric current on the coil. Several designs were tried out from the results of this study. Later can be used as the basis of designing a LieYo hydro generator.
Keywords: waterwheels, RPM, energy